2021
DOI: 10.1111/jace.17845
|View full text |Cite
|
Sign up to set email alerts
|

Influence of oxygen vacancies on core‐shell formation in solid solutions of (Na,Bi)TiO3 and SrTiO3

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 47 publications
(122 reference statements)
1
5
0
Order By: Relevance
“…Obviously, all samples present a well‐crystallized perovskite structure and no second phase can be observed, implying that Nb 5+ ions successfully dissolved into the BNBCST lattice to form a uniform solid solution. From Figure 2B, comparing the diffraction data of x = 0.15 composition with those of (Na 0.5 Bi 0.5 )TiO 3 (PDF#: 70−4760), BaTiO 3 (PDF#: 74–1963), SrTiO 3 (PDF#: 35−0734), and CaTiO 3 (PDF#: 75−2100) standard JCPDS cards, the BNBSCT‐0.15Nb displays a single pseudo‐cubic structure, which is consistent with other Nb‐doped perovskite ferroelectrics 28,29 . From the enlarged image at around 46° in Figure 2A, the (200) peak slightly moves to low angles with the Nb content increasing from 0.01 to 0.25, which indicates that Nb doping can lead to the expansion of unit cells.…”
Section: Resultssupporting
confidence: 77%
“…Obviously, all samples present a well‐crystallized perovskite structure and no second phase can be observed, implying that Nb 5+ ions successfully dissolved into the BNBCST lattice to form a uniform solid solution. From Figure 2B, comparing the diffraction data of x = 0.15 composition with those of (Na 0.5 Bi 0.5 )TiO 3 (PDF#: 70−4760), BaTiO 3 (PDF#: 74–1963), SrTiO 3 (PDF#: 35−0734), and CaTiO 3 (PDF#: 75−2100) standard JCPDS cards, the BNBSCT‐0.15Nb displays a single pseudo‐cubic structure, which is consistent with other Nb‐doped perovskite ferroelectrics 28,29 . From the enlarged image at around 46° in Figure 2A, the (200) peak slightly moves to low angles with the Nb content increasing from 0.01 to 0.25, which indicates that Nb doping can lead to the expansion of unit cells.…”
Section: Resultssupporting
confidence: 77%
“…Unfortunately, the negative strain (Sneg) and low positive strain in the BNT systems are not favorable to the application of precise actuators [3][4][5][6][7]. To solve these problems, many strategies were proposed to improve the strain performances, including core-shell structure, grain size engineering, defect modulation, and texturing techniques [8][9][10][11][12][13][14][15][16][17][18][19]. For instance, Steiner.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Steiner. et al constructed the core-shell structures in SrTiO3-modified BNT ceramics, and found that the oxygen vacancies could enhance the Sr 2+ ions diffused into the core region and transformed the ferroelectric behavior to ergodic relaxor states, which effectively promoted the strain response of d33 * [13]. By introducing plate-like NaNbO3 templates into the BNT-ST system, the grain orientation growth was successfully induced and the relaxor ergodicity was enhanced, and a high strain of ~0.39% was achieved in the <001>-oriented ceramics at the electric field of 60•kV/cm [14].…”
Section: Introductionmentioning
confidence: 99%
“…Koch et al 19 reported a delicate interplay of defect complex formation, phase transitions, and phase coexistence using the temperature dependence of ionic conductivity in acceptor-doped BNT-based ceramics. Steiner et al 27 mentioned that oxygen vacancies play a crucial role in the chemical homogeneity and electric properties of NBT-ST-based ceramics. Jia et al 28 discussed the effect of defect dipoles (formed from oxygen vacancies due to B-site doping) on relaxor FE BNT-BT ceramics after poling.…”
Section: Introductionmentioning
confidence: 99%